Pharmacology and clinical pharmacology of methylarginines used as inhibitors of nitric oxide synthases - Kittel, Anja; Maas, Renke (Current Pharmaceutical Design, 2014)
The methylarginines asymmetric dimethylarginine (ADMA) and monomethylarginine (L-NMMA) are endogenously formed inhibitors of nitric oxide synthases (NOS), which have extensively been investigated as risk markers and used as pharmacological tools to study the L-arginine-nitric oxide (NO) pathway in vitro and in vivo. It is the aim of the present review to summarize the clinical and experimental data on the pharmacological properties that are of relevance when planning and conducting experiments and clinical studies involving methylarginines. Key pharmacodynamic and pharmacokinetic data including IC50 values of ADMA and L-NMMA for NOS isoforms and transport proteins, as well as metabolism by dimethylarginine dimethylaminohydrolases (DDAH1 and DDAH2) and alanine-glyoxylate aminotransferase 2 (AGXT2) are discussed.
EVALuna2:8675